Incentives for Retailer Forecasting: Rebates vs. Returns - Taylor, Terry A.; Xiao, Wenqiang (Management Science, 2009)
This paper studies a manufacturer that sells to a newsvendor retailer who can improve the quality of her demand information by exerting costly forecasting effort. In such a setting, contracts play two roles: providing incentives to influence the retailer's forecasting decision and eliciting information obtained by forecasting to inform production decisions. We focus on two forms of contracts that are widely used in such settings and are mirror images of one another: a rebates contract, which compensates the retailer for the units she sells to end consumers, and a returns contract, which compensates the retailer for the units that are unsold. We characterize the optimal rebates contracts and returns contracts. Under rebates, the retailer, manufacturer, and total system may benefit from the retailer having inferior forecasting technology; this never occurs under returns. Although one might conjecture that returns would be inferior because its provision of “insurance” would discourage the retailer from forecasting, we show that returns are superior.